TECHNICAL EFFICIENCY ANALYSIS OF PUBLIC HEALTH CENTRE IN MATARAM REGENCY IN 2016 - Sri Sulistiowati; Iwan Harsono; Prayitno Basuki (Jurnal Ekonomi dan Studi Pembangunan, 2017)
The focus of this study is measuring relative efficiency of 11 public health centers in Mataram regency in 2016, by using nonparametric approach Data Envelopment Analysis (DEA). DEA is chosen because it is able to handle more input and output variables. This study uses output-oriented model. Input variables of health medical labors and other health labors, cost of salary and health operational supporting fund. Output variables of confinement scope that is helped by health labors, the scope of children under five pneumonia, the scope of lung TB BTA, the scope of basic immunization, the scope of early detecting cervix cancer and breast cancer (CA mamae). The results are seven public health centers classified as technically efficient and the remaining classified as technically inefficient in 2016 for the public health centers which are technically inefficient can be improved by increasing output variable based on DEA.Keywords: Relative efficiency, Public health center, DEAJEL Classification: G31, I15